Intensity of larval diapause in the bamboo borer, Omphisa fuscidentalis - Singtripop T. (2014)
Larvae of the bamboo borer, Omphisa fuscidentalis, enter larval diapause in September and pupate in the following June (Singtripop et al., 1999). We examined the changes in the responses of larvae to exogenous 20-hydroxyecdysone (20E) in order to estimate the progress of diapause development. In this respect, we adopted two terms, responsiveness and sensitivity of larvae to 20E. Responsiveness was estimated by the percentage of larvae that pupated, and sensitivity was evaluated by the duration from the day of 20E injection to pupation. The responsiveness of larvae declined gradually from September to November when larvae were least responsive to 20E, and then increased markedly from January to February. This indicates that the intensity of diapause increases from September to November and terminated gradually thereafter. Thus the sequence of events as the larval responses to 20E is characterized by a V-shaped curve. Sensitivity of larvae to 20E was at the same level from September to December, and increased remarkably from December to January. The abrupt increase in the sensitivity occurred one month earlier than the bottom of the V-shaped curve of larval responsiveness, suggesting that the increases in the responsiveness and sensitivity in the latter hall of diapause may be brought about by respective mechanisms.